2017
DOI: 10.1002/anie.201611314
|View full text |Cite
|
Sign up to set email alerts
|

Boraformylation and Silaformylation of Allenes

Abstract: The boraformylation of allenes with B (pin) and a formate ester as boron and formyl source, respectively, proceeds in the presence of a copper catalyst. The reaction selectively affords the corresponding β-boryl β,γ-unsaturated aldehydes in good to high yields. Furthermore, the silaformylation of allenes was achieved with a formate ester and PhMe Si-B(pin) as the silicon source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 60 publications
0
34
1
5
Order By: Relevance
“…Hoveyda et al described the asymmetric protoboration of these substrates catalyzed by chiral NHCcopper complexes. [66] With the appropriate choice of reagents, boraformylation, [67] boroacylation, [68,69] boraalkoxyoxalylation, [69] or asymmetric diboration [70] have been reported with different copper(I)-phosphine catalytic systems.…”
Section: Scheme12 A-hydroboration Of Terminal Alkynesmentioning
confidence: 99%
“…Hoveyda et al described the asymmetric protoboration of these substrates catalyzed by chiral NHCcopper complexes. [66] With the appropriate choice of reagents, boraformylation, [67] boroacylation, [68,69] boraalkoxyoxalylation, [69] or asymmetric diboration [70] have been reported with different copper(I)-phosphine catalytic systems.…”
Section: Scheme12 A-hydroboration Of Terminal Alkynesmentioning
confidence: 99%
“…[8] Asymmetric copper-catalyzed borylations represent ap owerful tool for the synthesis of optically active organoboron compounds. [9] We and other groups have reported the asymmetric synthesis of allylboron compounds via the asymmetric boryl substitution of allylic compounds (Scheme 1a). [10] Thea llylboration of aldehydes with enantioenriched allylboronates generally proceeds in ah ighly stereospecific manner.…”
mentioning
confidence: 99%
“…We found that boraformylation of allenes could be achieved by employing B2(pin)2 and a formate ester as the boron and formyl sources, respectively, in the presence of a copper catalyst 26) . Reaction of 3-methyl-1,2-nonadiene (11a), B2(pin)2, and hexyl formate (1g) was carried out at 50 by employing 3.0 mol% of CuOAc and 4.0 mol% of a ligand in toluene (Scheme 13).…”
Section: C U -C a T A L Y Z E D B O R A F O R M Y L A T I O N A N Dmentioning
confidence: 99%